Acknowledgment to Reviewers 2021 - Balenović, Ivan (Forest Research Institute, Jastrebarsko, 2022)
The editors of South-east European forestry would like to express their sincere gratitude to the following reviewers for evaluating manuscripts in 2020. Their generous contributions of time and expertise are greatly appreciated. Reviewers who evaluated two or more manuscripts in 2020 are underlined.
Keywords: acknowledgment; reviewers in 2020